Examining Controls on Fluid Overpressure in Buried Basement Highs of Oceanic Crust: Implications for Permeability of the Astoria Fan - Thomas Kyritz; Glenn A. Spinelli; Robert N. Harris (Geochemistry, Geophysics, Geosystems, 2025)
Abstract Vigorous hydrothermal circulation in the basement aquifer of the oceanic crust homogenizes temperatures within the aquifer and generates fluid overpressures at the tops of buried basement highs. At a site ∼25 km seaward of the Cascadia subduction zone deformation front, fluid overpressure at the top of the buried MARGIN seamount drives vertical fluid seepage through sediment overlying the seamount and results in anomalously high heat flux at the seafloor. In this study, we use numerical models of coupled heat and fluid transport to investigate the sensitivity of fluid overpressures to sediment thickness and basement relief for a 2D buried basement ridge. For ∼8 Ma oceanic crust buried by low permeability sediment, we find that the overpressure at the summit of a basement ridge increases by ∼0.10 kPa per meter of burial depth and by ∼0.71 kPa per meter of basement relief. For a 3D system with a geometry similar to the MARGIN seamount buried by low permeability sediment, the modeled fluid overpressure at the top of the seamount is ∼996 kPa. However, the Astoria Fan sediment above the MARGIN seamount likely has relatively high permeability, permitting rapid vertical seepage, thereby reducing fluid overpressure maintained at the top of the seamount. An overpressure of 492 kPa at the summit of the buried seamount at the MARGIN site and a bulk permeability of the Astoria Fan sediments of 4 × 10−15 m2 are consistent with the seepage rate of 5.4 cm yr−1 estimated from the elevated heat flux.